UNIT 7.2 Immunoprecipitation. Issue 1 (1st June 2016) - Bonifacino, Juan S.; Gershlick, David C.; Dell'Angelica, Esteban C.
Abstract : Selective immunoprecipitation of proteins is a useful tool for characterizing proteins and protein‐protein interactions. Clear step‐by‐step protocols are provided for preparing lysates of cells and yeast under a variety of conditions, for binding the antibody to a solid matrix, and for performing the actual immunoprecipitation. An additional method is provided for increasing the specificity of the technique by reprecipitating the antigen with the same or a different antibody. © 2016 by John Wiley & Sons, Inc.